PENGARUH KONSENTRASI ALK(SO4)2 12H2O (ALUMINIUM POTASSIUM SULFAT) TERHADAP PERUBAHAN BUKAAN OPERKULUM DAN SEL JARINGAN INSANG IKAN NILA MERAH (Oreochromis niloticus) - Eryan Huri; Syafriadiman ' (Berkala Perikanan Terubuk, 2010)
This research was conducted since September until November 2008 atthe Water Quality Management and Paracyties and Desease of Fish LaboratoryFaculty of Fishery and Marine Science Riau University. The aims of this researchwas to identify the damage of gill tissue structure red tilapia (Oreochromisniloticus). This research using experimental method and use completed randomdesign 1 factor with 4 treatments and 3 replications. This research using red tilapiathe measure of 8-10 cm, weight 30-40 gram from the hatchery in Pekanbaru.Result of the research show the toxicant giving effect on gill structure changes ofred tillapia fish. Fish of treatment experience of the change of structure of gillnetwork, especially happened by the nekrosis, proliferasi cells, a few moltenlamella, haemorhage and there are worm, and also secondary lamella.Concentration of toxicant hence smaller footage and apart between secondarylamella of red tillapia fish. On the contrary, excelsior of concentration of toxicant,hence wide progressively secondary lamella of gill red tillapia fish. Result of theexperiments indicated that toxicant of the AlK(SO4)212H2O concentrations havean effect on the gills tissue structure of red tilapia. Concentrations of toxicantincrease caused the gills tissue structure came to be better.